Cash crops or cover crops? The reasons and barriers for adopting cover crops in the Southern Great Plains of Texas and Oklahoma - Jamar, Patrick; Fuller, Emily R.; Leggette, Holli R.; Lu, Peng; Wald, Dara M.; Berthold, Troy Allen; deVilleneuve, Stephanie (Frontiers in Sustainable Food Systems, 2025)
Water conservation practices such as cover crop adoption have been promoted as effective strategies to improve water quality and soil health. However, cover crop adoption rates have remained low in Texas. A better understanding of the barriers to farmer cover crop adoption can highlight new pathways, encouraging conservation practice adoption across regions of the U.S. Our study examined reasons and barriers to cover crop adoption, including farmers’ demographics and farm characteristics. Using guidance from social cognitive theory and the theory of social normative behavior, we also examined how personal, cognitive, and environmental factors shaped farmers’ behaviors. The data collection process took place starting May 5, 2022, and ending December 30, 2022. A random sample of 3,000 participants was selected from the 88 counties in the Southern Great Plains of Texas and Oklahoma, using the 2021 USDA farm payment payees’ online files. Data were collected using a cross-sectional survey to describe characteristics of farmer populations (e.g., farmers, ranchers, land managers). Results indicated adaptors were largely 51–70 years old (58.3%), female (55.6%), and white (94.4%), with a majority being highly educated [i.e., having a graduate (22.2%) or bachelor’s (36.1%) degree]. Moreover, adoption reasons increased as farmers attained smaller income amounts from agricultural products. Of farmers who adopted cover crops, 38.9% did not use irrigation while 22.2% irrigated between 81 and 100% of their farmed land. Most adopters (61.8%) farmed annual crops. Adopters and non-adopters were significantly different in their environmental and economic barrier perceptions for cover crop adoption. We conclude by discussing situational and economic factors driving these findings and providing opportunities for future research.